Analytical investigation of nonreciprocal response in 1D nonlinear photonic crystals - Ronger Lu (Nature Portfolio, 2017)
Abstract The nonreciprocal response of the SHG process in 1D periodical nonlinear photonic crystals with a defect embedded has been theoretically studied by solving the nonlinear coupled equations. The nonreciprocal response has been deduced analytically with the solution of non-reciprocity parameters obtained. The result shows that as the non-reciprocity approaches 100%, the crystal length and the input power needed increase at a logarithmic rate. Any target nonreciprocal response can be reached in this structure by adjusting the structure parameters.